Compounds with NO Inhibitory Effect from the Rattan Stems of Sinomenium acutum, a Kind of Chinese Folk Medicine for Treating Rheumatoid Arthritis. Issue 6 (27th May 2022) - Yu, Kuo; Sun, Ying; Xue, Lu; He, Jingtao; Li, Fangyi; Yin, Maojing; Li, Zheng; Yan, Xiaohui; Guo, Jialiang; Li, Guoqiang; Wang, Chunhua
Abstract: Three new alkaloids (1 –3 ), one new diphenyl ether (4 ) and fifteen known alkaloids (5 –19 ) were isolated from the rattan stems of Sinomenium acutum . Comprehensive analyses of HR‐ESI‐MS, 1D ( 1 H and 13 C), 2D‐NMR ( 1 H‐ 1 H COSY, HSQC, HMBC, NOESY), circular dichroism (CD), UV and IR revealed the structures and absolute configurations of these new compounds. The structures of other compounds were determined by comparison of their 1 H and 13 C‐NMR data with previous literature reports. By measuring the amount of NO produced, the anti‐inflammatory properties of the isolated compounds were studied. The results showed that compounds 4 and 5 had strong NO inhibitory activity. Abstract :